A case study of a hydride container performance applying non dimensional parameters - Silin, Nicolas (2014)
Many efforts have been done so far to understand sorption dynamics of hydride containers for hydrogen storage. Particularly, there are many articles in literature where experimental results for different hydride systems and container set-ups were successfully simulated using basically the same group of models. This fact is the base of a previous work where we defined a series of non dimensional parameters which may be used to estimate absorption time of hydride containers. In this work we compare estimated absorption times with experimental outcomes for a prototype hydride container. We performed non dimensional analysis of our finned container prototype at two scales, i.e.: overall or macroscopic container scale and pore or microscopic scale. We discuss about this simplified model approach that allows estimating, with few parameters, the reaction time of a complex-geometry prototype. The prototype container was designed according to the results of a numerical optimization that maximized the amount of hydrogen absorbed for a 3 min charging period. Experimental results indicate good agreement between estimated and experimental absorption time, making the non dimensional method a useful tool at preliminary stages of hydride container design.